A DYNAMIC MODEL OF TAXATION, CORRUPTION, AND PUBLIC INVESTMENT IN THE DYNASTIC CYCLE: THE CASE OF IMPERIAL CHINA. (17th March 2016) - Chan, Kenneth S.; Laffargue, Jean-Pierre
Abstract : This paper develops a stochastic growth model that reproduces the main stylized facts of Imperial China's dynastic cycle—in particular, the time path of taxation, public spending, and corruption and their attendant impacts on production and income distribution. In this model, the emperor uses part of his tax income to finance the building of public capital and administrative institutions. This "institutional capital" enhances the productivity of the economy and limits extortion by the county magistrates. The dynastic cycle is driven by random shocks to the authority of the emperor and his central administration, which change the efficiency of institutional capital.